Trichotillomania and repetitive behavior in bulimia nervosa - Christenson, G.A; Mitchell, J.E (The International journal of eating disorders, 1991)
Researchers have suggested a possible association between trichotillomania and bulimia nervosa. This study utilized a questionnaire to compare the prevalence of trichotillomania, other habits, self-injurious behaviors, and other impulse control behaviors in 65 subjects with bulimia nervosa and 40 controls. There was no difference in the prevalence of trichotillomania between the two populations. There was a trend towards a higher prevalence of compulsive stealing in subjects with bulimia nervosa.